“I Know What I Like” – Indecisiveness Is Unrelated to Behavioral Indicators of Evaluation Difficulties - Appel, Helmut; Englich, Birte; Burghardt, Juliane (Frontiers in Psychology, 2021)
Indecisiveness, the subjective inability to make satisfactory decisions, is a trait that has detrimental effects on acting effectively. Mechanisms underlying indecisiveness are largely unknown. In four studies, we tested the prediction that indicators of evaluation difficulty are negatively associated with indecisiveness in simple evaluations. Across studies, indecisiveness was measured via self-report while evaluation difficulties were derived behaviorally from three indicators: similarity of evaluations (i.e., standard deviation), evaluation duration (reaction times), and implicit evaluations (evaluative priming effect) using familiar everyday objects. Study 1 (N = 151) was based on attractiveness evaluations of portraits. Studies 2a (N = 201) and 2b (N = 211) used chocolate as evaluation objects and manipulated to what extent the evaluations were equivalent to a decision. In Study 3 (N = 80) evaluations were measured implicitly through evaluative priming using food pictures. Contrary to our predictions, indecisiveness showed no association to any indicator of evaluation difficulty, regardless of type of evaluation object, equivalence of evaluation and decision, and whether evaluation difficulty was based on explicit or implicit evaluations. All null findings were supported by Bayes factors. These counterintuitive results make a first step in investigating evaluation processes as potential mechanisms underlying indecisiveness, showing that for both explicit and implicit measurements, indecisiveness is not characterized by difficulties when evaluating familiar everyday objects.